A Comment on Uncertainty and Household Decisions - Block, M. K.; Heineke, J. M. (Review of Economic Studies, 1972)
M. K. Block, J. M. Heineke; A Comment on Uncertainty and Household Decisions12, The Review of Economic Studies, Volume 39, Issue 4, 1 September 1972, Pages 523–